Developing Markets for Recycled Organic Products in Florida - Mohammad Rahmani; Alan W. Hodges; Clyde F. Kiker (EDIS)
Issues on various aspects of recycled organic products are drawing increasing attention from public and private sectors. However, most of the attention is being paid to organic recycling as a potential means of reducing wastes going to landfills. It is obvious that conversion of organic solid wastes to various products will reduce disposal problems. This is EDIS document FE499, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published December 2004.